2020
DOI: 10.1111/poms.13225
|View full text |Cite
|
Sign up to set email alerts
|

Buyer Financing in Pull Supply Chains: Zero‐Interest Early Payment or In‐House Factoring?

Abstract: T his study investigates the efficacy of zero-interest early payment financing (alternatively referred to as early payment) and positive-interest in-house factoring financing in a pull supply chain with a capital-constrained manufacturer selling a product through a capital-abundant retailer. Early payment is the prepayment of a wholesale cost to the manufacturer, whereas in-house factoring is a loan service provided to the manufacturer by a branch financing firm of the same retailer. We find that the retailer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Even if supplier financing cannot fully coordinate the supply chain-other financing schemes such as in-house factoring fully coordinate the supply chain-in situations where bank loans are attractive to suppliers, it is still considered a better financing mode. Similar conclusions can be drawn when the manufacturer's production costs are not too high or when the information about the known supplier is better than that of the bank [16,17]. Compared with bank credit, the trade credit model in the supply chain can more effectively alleviate agency conflicts and enable retailers to achieve optimal inventory strategies at a lower cost without excessive investment under bank credit [18].…”
Section: Literature Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Even if supplier financing cannot fully coordinate the supply chain-other financing schemes such as in-house factoring fully coordinate the supply chain-in situations where bank loans are attractive to suppliers, it is still considered a better financing mode. Similar conclusions can be drawn when the manufacturer's production costs are not too high or when the information about the known supplier is better than that of the bank [16,17]. Compared with bank credit, the trade credit model in the supply chain can more effectively alleviate agency conflicts and enable retailers to achieve optimal inventory strategies at a lower cost without excessive investment under bank credit [18].…”
Section: Literature Reviewmentioning
confidence: 54%
“…Furthermore, the optimal strategy of the manufacturer and the non-green supplier satisfying (17) and ( 18) is shown below:…”
Section: The Model With Carbon Emission Limitsmentioning
confidence: 99%
“…Second, considering a quadratic production cost function in our model, we find that the retailer is willing to offer APM with high production cost coefficient which is different from the situation where the production yield of the manufacturer is certain. In the retailer financing supply chain where the yield is certain and linear production cost is considered, the retailer has no incentive to offer finance the manufacturer when the production cost is substantially high [32]. ird, the retailer is willing to offer APM when the manufacturer's initial capital is low.…”
Section: Discussionmentioning
confidence: 99%
“…ey examined the impact of the retailer's loss aversion level on financing decisions. Chen et al [32] compared three financing schemes, i.e., zero-interest early payment financing and positive-interest in-house factoring financing in a pull supply chain where the manufacturer is capital constrained. ey found that early payment financing is more attractive than bank financing for the retailer when the manufacturer's production cost is low.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation